2009
DOI: 10.1002/dvdy.21974
|View full text |Cite
|
Sign up to set email alerts
|

Epitope‐tagging Math5 and Pou4f2: New tools to study retinal ganglion cell development in the mouse

Abstract: Although immunological detection of proteins is used extensively in retinal development, studies are often impeded because antibodies against crucial proteins cannot be generated or are not readily available. Here, we overcome these limitations by constructing genetically engineered alleles for Math5 and Pou4f2, two genes required for retinal ganglion cell (RGC) development. Sequences encoding a peptide epitope from haemagglutinin (HA) were added to Math5 or Pou4f2 in frame to generate Math5HA and Pou4f2HA all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
100
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(112 citation statements)
references
References 49 publications
12
100
0
Order By: Relevance
“…Consistent with this notion, most Pou4f2/Isl1-expressing cells in the NBL (>80%) were Atoh7 + , as indicated by colabeling of Pou4f2 and HA in the Atoh7 tTA/HA ;tetO-P&I retina (Fig. S1 E-G) in which Atoh7 expression was marked by an HA tag (10). However, many Atoh7-expressing cells did not express Pou4f2, indicating a lapse between the expression of tTA from the Atoh7 promoter and the activation of the tetO-P&I transgene.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Consistent with this notion, most Pou4f2/Isl1-expressing cells in the NBL (>80%) were Atoh7 + , as indicated by colabeling of Pou4f2 and HA in the Atoh7 tTA/HA ;tetO-P&I retina (Fig. S1 E-G) in which Atoh7 expression was marked by an HA tag (10). However, many Atoh7-expressing cells did not express Pou4f2, indicating a lapse between the expression of tTA from the Atoh7 promoter and the activation of the tetO-P&I transgene.…”
Section: Resultssupporting
confidence: 68%
“…S1D). Because Atoh7 is active in a larger population of cells than Pou4f2 and Isl1 in the NBL of wild-type retinas (10), the increased number of Pou4f2-and Isl1-expressing cells indicated that tTA from the Atoh7 tTA allele activated the tetO-P&I transgene and thus produced Pou4f2 and Isl1 in RPCs that normally express Atoh7. Consistent with this notion, most Pou4f2/Isl1-expressing cells in the NBL (>80%) were Atoh7 + , as indicated by colabeling of Pou4f2 and HA in the Atoh7 tTA/HA ;tetO-P&I retina (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The floxed Oc1 allele (Oc1 flox ) and the Six3-cre transgenic line have been described previously (Furuta et al, 2000;Zhang et al, 2009). The Ptf1a Ϫ (Ptf1a cre ) mice (Fujitani et al, 2006) were obtained from MMRRC-UNC (Stock number: 000435-UNC). All lines were maintained in C57BL/6ϫ129 mixed background.…”
Section: Methodsmentioning
confidence: 99%